Genome-Wide Association Study of Serum 25-Hydroxyvitamin D in US Women - O'Brien, Katie M.; Sandler, Dale P.; Shi, Min; Harmon, Quaker E.; Taylor, Jack A.; Weinberg, Clarice R. (Frontiers in Genetics, 2018)
Genetic factors likely influence individuals' concentrations of 25-hydroxyvitamin D [25(OH)D], a biomarker of vitamin D exposure previously linked to reduced risk of several chronic diseases. We conducted a genome-wide association study of serum 25(OH)D (assessed using liquid chromatography-tandem mass spectrometry) and 386,449 single nucleotide polymorphisms (SNPs). Our sample consisted of 1829 participants randomly selected from the Sister Study, a cohort of women who had a sister with breast cancer but had never had breast cancer themselves. 19,741 SNPs were associated with 25(OH)D (p<0.05). We re-assessed these hits in an independent sample of 1534 participants who later developed breast cancer. After pooling, 32 SNPs had genome-wide significant associations (p<5x10-8). These were located in or near GC, the vitamin D binding protein, or CYP2R1, a cytochrome P450 enzyme that hydroxylates vitamin D to form 25(OH)D. The top hit was rs4588, a missense GC polymorphism associated with a 3.5 ng/mL decrease in 25(OH)D per copy of the minor allele (95% confidence interval [CI]: -4.1, -3.0; p=4.5x10-38). The strongest SNP near CYP2R1 was rs12794714, a synonymous variant (p=3.8x10-12; =1.8 ng/mL decrease in 25(OH)D per minor allele [CI: -2.2, -1.3]). Serum 25(OH)D concentrations from samples collected from some participants 3-10 years after baseline (811 cases, 780 non-cases) were also strongly associated with both loci. These findings augment our understanding of genetic influences on 25(OH)D and the possible role of vitamin D binding proteins and cytochrome P450 enzymes in determining measured levels. These results may help to identify individuals genetically predisposed to vitamin D insufficiency.